Jeḳuti'el Zalman ha-Kohen and first non-direct remarks on the Czech phonetics - Ulicna, Lenka (Bohemica Olomucensia, 2012)
Jeḳuti'el Zalman ha-Kohen was well-known Ashkenaz grammarian who described and commented the Hebrew phonetics. There are many phonetic remarks in his manuscript'Ejn ha-ḳore (The eye of reader) commenting and critising contemporary practices in pronunciation and recitation of Hebrew biblical text. He deals e.g. with the stress in Hebrew (secondary stress, meteg, included), with phonetic realisation of Hebrew consonants and vowels and partially with Hebrew inflection and word formation. In this way he brings interesting non-direct evidence about phonetics of Czech that interferred with the Hebrew.